Lack of Humoral Immunity Against Glucosaminidase Is Associated with Postoperative Complications in Staphylococcus aureus Osteomyelitis. (4th November 2020) - Kates, Stephen L.; Owen, John R.; Beck, Christopher A.; Xie, Chao; Muthukrishnan, Gowrishankar; Daiss, John L.; Schwarz, Edward M.
Abstract : Background: Glucosaminidase (Gmd) is known to be a protective antigen in animal models of Staphylococcus aureus osteomyelitis. We compared the endogenous anti-Gmd antibody levels in sera of patients with culture-confirmed S. aureus bone infections to their sera at 1 year after operative treatment of the infection. Methods: A novel global biospecimen registry of 297 patients with deep-wound culture-confirmed S. aureus osteomyelitis was analyzed to assess relationships between baseline anti-Gmd serum titers (via custom Luminex assay), known host risk factors for infection, and 1-year postoperative clinical outcomes (e.g., infection control, inconclusive, refracture, persistent infection, septic nonunion, amputation, and septic death). Results: All patients had measurable humoral immunity against some S. aureus antigens, but only 20 patients (6.7%; p < 0.0001) had high levels of anti-Gmd antibodies (>10 ng/mL) in serum at baseline. A subset of 194 patients (65.3%) who completed 1 year of follow-up was divided into groups based on anti-Gmd level: low (<1 ng/mL, 54 patients; 27.8%), intermediate (<10 ng/mL, 122 patients; 62.9%), and high (>10 ng/mL, 18 patients; 9.3%), and infection control rates were 40.7%, 50.0%, and 66.7%, respectively. The incidence of adverse outcomes in these groups was 33.3%, 16.4%, and 11.1%, respectively. Assessing anti-Gmd level as a continuous variable showed a 60% reduction in adverse-event odds (p = 0.04) for every tenfold increase in concentration. No differences in patient demographics, body mass index of >40 kg/m 2, diabetes status, age of ≥70 years, male sex, Charlson Comorbidity Index of >1, or Cierny-Mader host type were observed between groups, and these risk factors were not associated with adverse events. Patients with low anti-Gmd titer demonstrated a significant 2.68-fold increased odds of adverse outcomes (p = 0.008). Conclusions: Deficiency in circulating anti-Gmd antibodies was associated serious adverse outcomes following operative treatment of S. aureus osteomyelitis. At 1 year, high levels of anti-Gmd antibodies were associated with a nearly 3-fold increase in infection-control odds. Additional prospective studies clarifying Gmd immunization for osteomyelitis are needed. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.